2006
DOI: 10.5713/ajas.2006.587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Bacillus-based Probiotic on Growth Performance, Nutrients Digestibility, Blood Characteristics and Fecal Noxious Gas Content in Finishing Pigs

Abstract: This study was conducted to evaluate the effects of supplementation with bacillus-based probiotic (Bacillus subtilis, 1.0×10 7 CFU/g; Bacillus coagulans, 2.0×10 6 CFU/g and Lactobacillus acidophilus, 5.0×10 6 CFU/g) on finishing pigs growth performance, nutrients digestibility, blood characteristics and fecal noxious gas content and to determine the optimal addition level of this probiotic preparation. A total of forty eight pigs with an initial body weight (BW) of 90.60±2.94 kg were allotted to three dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 36 publications
12
61
4
1
Order By: Relevance
“…This hypothesis is strength by Ferket et al (2002), who suggested that probiotics could indirectly reduce environmental pollutants from animal manure by improving feed efficiency, nutrient retention and the intestinal microbiotia ecosystem. However, no difference was observed on the blood characteristic in the current study, which is in agreement with our previous study (Chen et al 2006), which suggested that no difference was observed with probiotic supplementation in pigs. In contrast, Cho et al (2005) suggested that red blood cell was improved with probiotics supplementation.…”
Section: Effect Of Probioticssupporting
confidence: 93%
See 1 more Smart Citation
“…This hypothesis is strength by Ferket et al (2002), who suggested that probiotics could indirectly reduce environmental pollutants from animal manure by improving feed efficiency, nutrient retention and the intestinal microbiotia ecosystem. However, no difference was observed on the blood characteristic in the current study, which is in agreement with our previous study (Chen et al 2006), which suggested that no difference was observed with probiotic supplementation in pigs. In contrast, Cho et al (2005) suggested that red blood cell was improved with probiotics supplementation.…”
Section: Effect Of Probioticssupporting
confidence: 93%
“…Recently, the application of probiotics had received considerable attention in the discussion about developing suitable alternative for antibiotic growth promoters in the pig industry (Chen et al 2006;Meng et al 2010;. However, the effect of probiotics supplementation in practice is highly inconsistent because of the different diet composition, strain differences, dose level, age of the animal, as well as its interactions with environmental factors (Loh et al, 2008;Khan, Yousaf, et al 2011;Khan, Atif, et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In their findings, they reported that piglets fed probiotics showed higher concentration of IgG than piglets fed treatment without probiotics. On contrary, Chen et al (2005) reported different result when studied the effect of dietary probiotics on growth performances, nutrient digestibility, blood characteristics and fecal noxious gas content in growing pigs. In their findings, they reported IgG concentration was not affected by dietary treatment of complex probiotics.…”
Section: Treatmentsmentioning
confidence: 98%
“…They cannot colonize in the gastrointestinal tract; but stimulate the growth of Lactobacilli through production of catalase and subtilisin (Hosoi et al, 2000). Several studies reported improvements in growth performance (Huang et al, 2004;Alexopoulos et al, 2004), nutrient digestibility (Shon et al, 2005;Chen et al, 2006), humoral and cell-mediated Ahmed et al 97 immune responses (Fernandes and Shahani, 1990; European food safety authority, 2010), and the microbial ecosystem (Huang et al, 2004;Baker et al, 2013) upon dietary supplementation with Lactobacillus or Bacillusbased probiotics, although inconsistencies in result have also been reported (Cromwell, 2001). The discrepancies observed can be attributed to different strains, dose levels, diet compositions, feeding strategies, age of animals, etc (Chesson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Langlois et al (1988) demonstrated that complete removal of antibiotics from animal production diminished resistance of lactose-fermenting fecal coliform bacteria. However, that has put tremendous pressure on the livestock industry to identify viable therapeutic alternatives against food borne pathogens, such as probiotics, which have used successfully in livestock feeds (Alexopoulos et al, 2004;Chen et al, 2005Chen et al, , 2006. Probiotics refer to a group of non-pathogenic organisms that, when ingested in sufficient number, have beneficial effects on the health of the host (Reid et al, 2003).…”
Section: Introductionmentioning
confidence: 99%